KEPEMIMPINAN DIGITAL 4.0: KAJIAN SISTEMATIS KONSEPTUALISASI DAN PRAKTIK DALAM PENDIDIKAN - Saragih, Abdul Hasan; K, Abdul Hamid; Sugiharto, Sugiharto; Nasution, Awal Kurnia Putra; Ananda, Ricki; Bangun, Oktaviana; Siregar, Iqbal Kamil; Efendi, Bachtiar; Sembiring, Rafika Sari Br (STKIP Pesisir Selatan, 2025)
This study presents a comprehensive analysis of the evolution of digital leadership in education, tracing its development from the initial concept of e-leadership to Leadership 4.0 amid the era of digital transformation and artificial intelligence (AI).